Nutrition and Metabolism in Sports, Exercise and Health - Kang, Jie (London : Taylor and Francis, 2018)
"The second edition of Nutrition and Metabolism in Sports, Exercise and Health offers a clear and comprehensive introduction to sport and exercise nutrition, integrating key nutritional facts, concepts and dietary guidelines with a thorough discussion of the fundamental biological science underpinning physiological and metabolic processes. Informed by the latest research in this fast-moving discipline, the book includes brand-new sections on, amongst others: Cellular structure for metabolism Alcohol and metabolism Uncoupling protein and thermogenesis Dietary guidelines from around the world Nutrient timing Protein synthesis and muscle hypertrophy Protein supplementation Ergogenic effects of selected stimulants Nutritional considerations for special populations Dehydration and exercise performanceEach chapter includes updated pedagogical features, including definitions of key terms, chapter summaries, case studies, review questions and suggested readings. A revised and expanded companion website offers additional teaching and learning features, such as PowerPoint slides, multiple-choice question banks and web links. No book goes further in explaining how nutrients function within our biological system, helping students to develop a better understanding of the underlying mechanisms and offering the best grounding in applying knowledge to practice in both improving athletic performance and preventing disease. As such, Nutrition and Metabolism in Sports, Exercise and Health is essential reading for all students of sport and exercise science, kinesiology, physical therapy, strength and conditioning, nutrition or health sciences."--Provided by publisher.
chapter 1 Introduction / Jie Kang -- chapter 2 Macronutrients -- Carbohydrates / Jie Kang -- chapter 3 Macronutrients -- Lipids / Jie Kang -- chapter 4 Macronutrients -- Proteins / Jie Kang -- chapter 5 Micronutrients -- Vitamins / Jie Kang -- chapter 6 Micronutrients -- Minerals and water / Jie Kang -- chapter 7 Digestion and absorption / Jie Kang -- chapter 8 Energy and energy-yielding metabolic pathways / Jie Kang -- chapter 9 Nutrients metabolism / Jie Kang -- chapter 10 Guidelines for designing a healthy and competitive diet / Jie Kang -- chapter 11 Ergogenic aids and supplements / Jie Kang -- chapter 12 Nutrition and metabolism in special cases / Jie Kang -- chapter 13 Measurement of energy consumption and output / Jie Kang -- chapter 14 Body weight and composition for health and performance / Jie Kang -- chapter 15 Energy balance and weight control / Jie Kang -- chapter 16 Thermoregulation and fluid balance / Jie Kang.
Keywords: Athletes -- Nutrition; Exercise -- Physiological aspects; Nutrition; Sports medicine; Sports -- Physiological aspects; Exercise Physiology; Physiology of Sport; Sports Nutrition